2017
DOI: 10.1073/pnas.1712305114
|View full text |Cite
|
Sign up to set email alerts
|

Top-down modulation of sensory cortex gates perceptual learning

Abstract: Practice sharpens our perceptual judgments, a process known as perceptual learning. Although several brain regions and neural mechanisms have been proposed to support perceptual learning, formal tests of causality are lacking. Furthermore, the temporal relationship between neural and behavioral plasticity remains uncertain. To address these issues, we recorded the activity of auditory cortical neurons as gerbils trained on a sound detection task. Training led to improvements in cortical and behavioral sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
108
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 93 publications
16
108
3
Order By: Relevance
“…We further provide evidence for training-induced neurophysiological changes in sensory encoding that relate to behavioral stability, and endure beyond a period of intensive training. Our findings are in support of an emerging view that auditory perceptual learning is mediated by top-down processes that shape sensory signals through later learning phases [30]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We further provide evidence for training-induced neurophysiological changes in sensory encoding that relate to behavioral stability, and endure beyond a period of intensive training. Our findings are in support of an emerging view that auditory perceptual learning is mediated by top-down processes that shape sensory signals through later learning phases [30]. …”
Section: Discussionsupporting
confidence: 88%
“…In line with this idea, animal models have revealed top-down gated sensory enhancement of selective features of incoming acoustic stimuli following extensive behaviorally-relevant training [2628]. Our findings suggest that native listeners and over-trained learners may be able to operate at the level of category-based perception and reach down to lower-levels of the sensory hierarchy for tuning of behaviorally-relevant signals, depending on the nature of the task [29, 30]. Learners who demonstrated better perceptual identification of tone categories (thought to reflect higher-level attention-driven processes [31]) at the novice learning phase, took fewer days to reach the learning criterion (Figure 3C).…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, we propose that the representation of stimulus features in sensory cortex, such as tone frequency in A1, does not depend alone on the transmission process of the sensory information via the primary sensory pathways, but is significantly modulated by the behavioral need and the behavioral relevance of a stimulus. Such influence is based presumably on higher order top-down inputs from, for instance, parietal and frontal areas (Caras and Sanes, 2017;Polley et al, 2006;Rodgers and DeWeese, 2014;Runyan et al, 2017;Steinmetz et al, 2019).…”
Section: Supragranular Layer Activity Better Classifies the Stimulus mentioning
confidence: 99%
“…However, the underlying integrative circuit mechanisms are still only partially understood. In the case of the auditory system, ample evidence has revealed that the primary auditory cortex (A1) integrates sensory information with other contextual and motor signals and further reflects higher cognitive demands responsible for prediction (Kumar et al, 2011;Parras et al, 2017;Town et al, 2018), choice accuracy (Niwa et al, 2012;Caras & Sanes, 2017), and auditory-guided decision making (Brosch et al, 2005;King et al, 2018;Ohl and Scheich, 2005;Tsunada et al, 2015). The salience of behaviorally relevant sounds further critically depends on the exact reinforcement regimes and task rules (Bagur et al, 2018;David et al, 2012;Huang et al, 2019), which renders the auditory cortex a multifarious integrative circuit.…”
Section: Introductionmentioning
confidence: 99%
“…In sensory systems, improved perception can be achieved through practice in specific sensory discrimination tasks, a process known as perceptual learning (PL) (Caras and Sanes, 2017). To test whether PL is associated with changes in PV expression in A1 we trained rats using an adaptive auditory oddball discrimination task (Figure 1A).…”
Section: Transient Downregulation Of Pv Expression Associated With Trmentioning
confidence: 99%